Visionary Leadership: Building The Future Through Vision and Innovation - Arkaan, Muhammad Zaidaan; Qomariyah, Nurul; Annisa, Nabila Nur; Nuriya, Intan Tirza (IAIN Syekh Nurjati Cirebon, 2024)
Visionary leadership is a managerial approach that emphasizes the development of transformational visions to effectively guide organizations toward achieving their goals. This study aims to identify the characteristics and implementation strategies of visionary leadership, particularly in the context of education. A qualitative descriptive method with a literature review approach was employed, analyzing relevant academic sources. The findings reveal that visionary leaders possess characteristics such as forward-thinking, the courage to make strategic decisions, innovation, effective communication, and adaptability to change. In the educational sector, visionary leaders play a critical role in fostering innovative learning ecosystems, empowering educators, and inspiring students to reach their full potential. Implementation strategies involve formulating clear visions, transforming them into concrete actions, and fostering collaboration with all stakeholders. The study concludes that visionary leadership serves as a strategic solution to navigate global dynamics and ensure organizational sustainability. Its implications highlight the need to adopt this approach to enhance educational institutions' quality and prepare future generations to be competitive.Keywords: Visionary leadership, vision, innovation, futureKepemimpinan visioner merupakan pendekatan manajerial yang mengedepankan kemampuan menciptakan visi transformasional guna mengarahkan organisasi menuju tujuan secara efektif. Penelitian ini bertujuan mengidentifikasi karakteristik dan strategi implementasi kepemimpinan visioner, khususnya dalam konteks pendidikan. Metode penelitian yang digunakan adalah deskriptif kualitatif dengan pendekatan studi literatur, yang menelaah berbagai sumber akademik relevan. Hasil penelitian menunjukkan bahwa pemimpin visioner memiliki karakteristik seperti pandangan jauh ke depan, keberanian mengambil keputusan strategis, inovasi, komunikasi efektif, serta adaptasi terhadap perubahan. Dalam dunia pendidikan, pemimpin visioner berperan penting dalam menciptakan ekosistem pembelajaran inovatif, memberdayakan tenaga pendidik, dan menginspirasi peserta didik untuk mencapai potensi maksimalnya. Implementasi strategi melibatkan proses perumusan visi yang jelas, transformasi visi menjadi aksi konkret, serta kolaborasi dengan seluruh pemangku kepentingan. Kesimpulan penelitian ini menegaskan bahwa kepemimpinan visioner adalah solusi strategis dalam menghadapi dinamika global dan memastikan keberlanjutan organisasi pendidikan. Implikasinya, pendekatan ini perlu diadopsi untuk meningkatkan kualitas institusi pendidikan dan mempersiapkan generasi masa depan yang kompetitif.Kata kunci: Kepemimpinan visioner, visi, inovasi, masa depan